BOOK REVIEWS - Lindholm, Richard W. (Journal of Finance, 1955)
Book reviewed in this article: Shareholder Democracy: A Broader Outlook for Corporations . By F rank D. E merson and F ranklin C. L atcham . Le Profit des Grandes Enterprises Américaines . By H ans S taub . Mobile Homes: The Growth and Business Practices of the Industry . By T aylor W. M eloan . Financing the Instalment Purchases of the American Family . By C lyde W. P helps . Group Annuities . By K enneth B lack , J r . Fundamentals of Private Pensions . By D an M c G ill . Convertibility and Foreign Trade . By J. F. G aston , F. W. J ones , H. P. D ryer , and H. B odansky . The International Bank for Reconstruction and Development, 1946–1953 . By I nternational B ank for R econstruction and D evelopment . The Dollar Dilemma: Perpetual Aid to Europe? By M elchior P alyi . Individuals' Saving: Volume and Composition . By I rwin F riend with the assistance of V ito N atrella . Planning Your Financial Independence . By J ohn E. L eibenderfer . Research in the Capital and Securities Markets. Economic Fluctuations: An Analysis of Business Cycles and Other Economic Fluctuations . By M aurice W. L ee . Money and Banking in British Colonial Africa . By W. T. N ewlyn and D. C. R owan . Money, Banking and the Financial System . By M ilton L. S tokes and C arl T. A rlt . British Public Finances, 1880–1952 . By U rsula K. H icks . A Century and a Half of Federal Expenditures . By M. S lade K endrick , assisted by M ark W ehle . Income Redistribution and Social Policy . Edited by A lan T. P eacock . Cutting Your Unemployment Taxes: A Practical Guide to Minimizing Unemployment Compensation Costs . By R ichard J. P otter . The Budgetary Process in the United States . By A rthur S mithies . New Rapid Tax Depreciation: How To Use It Profitably . By W illard F. S tanley . Experience in Urban Real Estate Investment: An Interim Report Based on New York City Properties . By L eo G rebler .